Organizational psychology in cross-cultural perspective - Silverthorne, Colin P. (Colin Patric) (New York University Press, 2005)
The last two decades have seen an explosive increase in the ethnic diversity of the workforce, growth in international business, and the emergence of many more multinational companies. The potential for problems as companies operate across borders and managers manage in countries which have different values, norms and cultural behaviors is great. By looking at organizational psychology in a cross-cultural context, we can gain an understanding of the challenges facing organizations and business today. This text breaks new ground in introducing organizational psychology from a cross cultural per.